Technology and their negative impact on students - Alajmi, Meaad (Technium Social Sciences Journal, 2022)
The paper studies the effect of technology on students ability to learn. It starts with an analytical framework of the main stages of learning: 1- experiencing, 2- conceptualizing, 3- analyzing and 4- applying. Then, it applies the framework on the use of technology in the Saudi Arabian educational environment. In addition, the paper suggests the possibility of a positive impact of technology on learning alongside the negative effects. The paper does so using the Saudi educational system as example. It finally concludes the potential of technology in improving the learning stages through better use of it.